A Miniaturized 4 : 1 Unequal Wilkinson Power Divider Using Artificial Transmission Lines and Double-Sided Parallel-Strip Lines - Wen Huang; Wei Ruan; Fei Tan (International Journal of Antennas and Propagation)
A 4 : 1 unequal Wilkinson power divider using microstrip artificial transmission lines (ATLs) is proposed. For the ATL, a series of meandered-line inductors, parallel-plate capacitors, and interdigital capacitors are employed. The designed power divider is composed of three ATLs, and a method has been proposed using technology of ATLs and double-sided parallel-strip lines (DSPSLs) to design line of high characteristic impedance. Microstrip line with very high characteristic impedance of over 150 Ω has been achieved by this method, which cannot be easily achieved by conventional transmission lines because of comparably thin conductor width. The fabricated 4 : 1 unequal power divider has good operational performance and occupies 55.3 mm×37.8 mm, which is only about 40% of area compared to a conventional one at 0.9 GHz.